Emigration and rural Ireland - Freeman, T. W. (Statistical and Social Inquiry Society of Ireland, 1946)
The decline in population in Eire during the past hundred years from 6,950,000 to 2,950,000 (1943) has been accompanied by revolutionary changes in land distribution and tenure and also by striking developments in agricultural technique. There have been measures of social amelioration in rural areas, notably during the last fifty years, that have left a vivid mark on the landscape and raised the standard of living throughout the country. Whether this would have been possible without emigration, or with emigration on a less widespread scale, is a debatable point that need only draw the comment here that if the middle nineteenth century was a period of overpopulation in Eire it is not inconceivable that the middle twentieth century may be a period of underpopulation, at least in the rural areas. Special consideration will be given in this paper to the main agricultural developments that have been accompanied by heavy emigration, to the changing balance of rural and urban populations and to the present staffing of farms in Eire.
Read on Thursday, 25th January, 1945
Keywords: Rural Ireland; Emigration; Land ownership; Rural population; 314.15